Hubungan antara Shyness dengan Problematic Internet Use pada Siswa SMP - Vioga, Meri; Aulia, Farah (AHKAM, 2023)
Problematic internet use is one of the phenomena that occurs related to internet use in junior high school students. The internet becomes an alternative for shyness individuals to satisfy and express their feelings, social and emotional needs, which are not expressed directly or offline. When internet use is uncontrolled and excessive, it will make individuals problematic. This study aims to determine the relationship between shyness and problematic internet use. The subjects of this study were junior high school students who used the internet excessively, consisting of 126 students, 38 male students (30.2%) and 88 female students (69.8%). This study used quantitative methods. The data obtained were analyzed using Pearson product moment correlation technique. The results showed that there is a significant relationship between shyness and problematic internet use with a correlation coefficient value of 0.744 and a significance value of 0.000. This value proves that there is a positive relationship between shyness and problematic internet use in junior high school students, the higher the level of shyness, the higher the level of problematic internet use experienced.